Penerapan squid game edukasi untuk meningkatkan penguasaan kosakata bahasa arab - Hariansyah Muhammad Siddik; Dedy Irawan; Umi Hijriyah; Damanhuri (Universitas KH. Mukhtar Syafaat, 2026)
Vocabulary mastery is one of the key factors in the success of Arabic language learning. However, the learning process, which is still dominated by conventional methods in class VIII T2 at MTs Muhammadiyah Sukarame Bandar Lampung, has caused some students to be unable to understand and use Arabic vocabulary optimally. This study aims to improve students’ mastery of Arabic vocabulary through the implementation of the interactive learning media Educational Squid Game (Honeycomb) in the learning process.This study employed the Classroom Action Research (CAR) method conducted in two cycles. The data collection techniques included observation, documentation, pre-tests, and post-tests. The results of the study showed an improvement in the students’ average scores and learning completeness from Cycle I to Cycle II. The average score increased from 79.46 in the pre-test to 84.75 in Cycle I, and reached 91.87 in the post-test of Cycle II. Classical learning completeness also increased significantly from 31% (pre-test) to 69% (Cycle I), and reached 91% at the end of Cycle II.In addition, the implementation of the interactive media Educational Squid Game (Honeycomb) was able to enhance students’ motivation, activeness, and engagement during the learning process. Therefore, the interactive media Educational Squid Game (Honeycomb) can be used as an effective, innovative, and enjoyable learning alternative to improve Arabic vocabulary mastery.